2005
DOI: 10.1038/sj.onc.1209141
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin plays an important role in hepatocellular carcinoma metastasis

Abstract: To identify genes associated with tumor metastasis in hepatocellular carcinoma (HCC), gene expression profiles between a pair of primary HCC (H2-P) and their matched metastatic HCC (H2-M) were compared. Overexpression of clusterin (CLU) was found in H2-M cells. To determine the roles CLU played in HCC metastasis, CLU was transfected into H2-P cells. Overexpression of CLU in H2-P cells increased cell migration by twofold in vitro and formation of metastatic tumor nodules in liver by eightfold in vivo. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 27 publications
3
112
1
Order By: Relevance
“…Further evidence that CLU might be oncogenic is that it can bind to and inactivate BAX, inhibiting druginduced apoptosis, and cooperate with c-MYC in transforming mammalian cells (Zhang et al, 2005). A tumourigenic effect of CLU in other types of epithelial cancer, like hepatocellular carcinoma, has been observed (Lau et al, 2006). In contrast with the hypothesis that CLU is a prostate oncogene, we and others have observed that CLU is down-regulated during human prostate cancer progression Rauhala et al, 2008).…”
Section: Introductionmentioning
confidence: 43%
“…Further evidence that CLU might be oncogenic is that it can bind to and inactivate BAX, inhibiting druginduced apoptosis, and cooperate with c-MYC in transforming mammalian cells (Zhang et al, 2005). A tumourigenic effect of CLU in other types of epithelial cancer, like hepatocellular carcinoma, has been observed (Lau et al, 2006). In contrast with the hypothesis that CLU is a prostate oncogene, we and others have observed that CLU is down-regulated during human prostate cancer progression Rauhala et al, 2008).…”
Section: Introductionmentioning
confidence: 43%
“…In HCC, CLU may play a significant role in tumorigenesis, progression and metastasis (25). Increased serum levels of CLU have been reported in lung cancer, breast cancer, ovarian cancer and HCC (8,24,(26)(27)(28). Ficolin belongs to the serum lectins and plays a crucial role in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer metastases, both intrahepatic and extrahepatic, are major factors causing the mortality of HCC patients. Recently, a number of cancer genes have been reported to be associated with the tumor metastasis in HCC, including CLU, KAI1, ROCK2 and TWIST [1][2][3][4]. Furthermore, we have previously identified several microRNAs that play critical roles in HCC metastasis, such as miR-30D, miR-151 and miR-210 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%